Strategic Antecedents of Business Agility in Education: Mediating Effects of Engagement and Moderating Role of Innovation Climate - Ninik probosari; Istiana Rahatmawati (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of Strategic Planning, Resource Flexibility, and Knowledge Sharing on Business Agility in educational institutions, by considering the role of Innovation Climate as a mediating variable and Employee Engagement as a moderating variable. A quantitative approach was used with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method on a number of respondents from higher education institutions. The results showed that Strategic Planning, Resource Flexibility, and Innovation Climate had a positive and significant effect on Business Agility, while Knowledge Sharing and Employee Engagement had no direct effect. In addition, Innovation Climate was proven to mediate the influence of Strategic Planning, Resource Flexibility, and Knowledge Sharing on Business Agility. These findings confirm that the agility of educational organizations depends on adaptive strategies, flexible resources, and an innovative climate that supports collaboration and continuous learning. Furthermore, the study highlights the importance of fostering a supportive innovation culture within academic environments, as it enables institutions to respond effectively to rapid environmental and technological changes. The integration of strategic planning and flexible resource management encourages continuous improvement, while innovation-driven practices enhance institutional responsiveness. Overall, this research contributes to a deeper understanding of how managerial and organizational factors collectively enhance agility in the education sector, providing practical implications for leaders aiming to strengthen innovation, adaptability, and sustainable performance in higher education institutions.